2022
DOI: 10.3390/ijms232315122
|View full text |Cite
|
Sign up to set email alerts
|

Antigen-Specific T Cells and SARS-CoV-2 Infection: Current Approaches and Future Possibilities

Abstract: COVID-19, a significant global health threat, appears to be an immune-related disease. Failure of effective immune responses in initial stages of infection may contribute to development of cytokine storm and systemic inflammation with organ damage, leading to poor clinical outcomes. Disease severity and the emergence of new SARS-CoV-2 variants highlight the need for new preventative and therapeutic strategies to protect the immunocompromised population. Available data indicate that these people may benefit fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 235 publications
0
1
0
Order By: Relevance
“…These CAR-T cells can be obtained after the specific manipulation of patients’ cells and, thus, can be used to prevent the entry of SARS-CoV-2 and also its associated variants despite the genome mutations that it could bear. In the same line, Nova et al [ 10 ] showed the efficient large-scale production of SARS-CoV-2-specific CD4 + and CD8 + T cells. Specifically, antigenic T-cells prepared by the IFN-γ cytokine capture system (CCS) have been classified as ATMPs, authorized for intended use by the EMA, and are currently used in critically ill SARS-CoV-2 patients.…”
mentioning
confidence: 96%
“…These CAR-T cells can be obtained after the specific manipulation of patients’ cells and, thus, can be used to prevent the entry of SARS-CoV-2 and also its associated variants despite the genome mutations that it could bear. In the same line, Nova et al [ 10 ] showed the efficient large-scale production of SARS-CoV-2-specific CD4 + and CD8 + T cells. Specifically, antigenic T-cells prepared by the IFN-γ cytokine capture system (CCS) have been classified as ATMPs, authorized for intended use by the EMA, and are currently used in critically ill SARS-CoV-2 patients.…”
mentioning
confidence: 96%